Surgery for rectal prolapse – a single centre experience - Danys, Donatas; Kavaliauskaitė, Gintarė; Žalimas, Algirdas; Žeromskas, Paulius; Mikalauskas, Saulius; Jotautas, Valdemaras; Poškus, Eligijus; Strupas, Kęstutis; Poškus, Tomas (Lietuvos chirurgija, 2016)
BackgroundNo consensus on the optimal procedure for repair of rectal prolapse (RP) exist. We present the results of our 10 year experience of Vilnius University Hospital Santariskiu Klinikos.Patients and methodsRetrospective review was performed of the patients, operated on for rectal prolapse between 2005 and 2016. Patients were divided into two groups – internal recal prolapse (IRP) and complete rectal prolapse (CRP). Perioperative data between two groups were analysed. Statistical data analysis was carried out using the SPSS 20.0 software. To assess the difference between rectal prolapse groups of statistical methods the χ2 test was used. Data were considered statistically significant at p < 0.05.Results89 patients between 2005 and 2016 underwent surgical treatment for rectal prolapse at our department. IRP group included 52 (58,4%), CRP – 37 (41,6%) patients. The male/female ratio was 1/6,4, the mean age was 58,3±15,2 years. Defecography was performed for 29 (32,6%)patients in IRP group and for 12 (13,5%) – in CRP group (p
Keywords: rectal prolapse; rectopexy; resection; laparoscopy